Diseño e implementación de un sistema de visión artificial basado en redes neuronales. - Oliveira Botello, Santiago (Ingeniería, 1999)
It 's been implemented a visual processing system based on biological models. Three independent different stages have been succesfully put together: figure-ground separation (FGS), invariant filter (What y Where filter) and a categorization system (Fuzzy ART), which working as a whole, allow the position, orientation and scale invariant automatic recognition of figures in a given scene.